The potential of naturalistic driving for in-depth understanding of driver behavior: UDRIVE results and beyond. (November 2019) - van Nes, Nicole; Bärgman, Jonas; Christoph, Michiel; van Schagen, Ingrid
Highlights: European naturalistic driving data reveal behavioral differences across countries. European drivers do not necessarily behave like U.S. drivers. European drivers use their mobile phones less while driving than U.S. drivers. The UDRIVE dataset provides more in depth understanding of driver behavior. Introduction of the conceptual Framework for Naturalistic Driving Studies (FNDS). FNDS gives insight in scope of study in the relation to sample and data collected. Abstract: Within the UDRIVE project, a rich cross-European naturalistic driving database was created which includes everyday driving data on car and truck drivers and powered two-wheeler riders. The database provides extensive, reliable insights into driving behavior in real traffic as a foundation for improving the safety and sustainability of European road traffic. This paper discusses the characteristics of the data in the UDRIVE database—elucidating key methodological choices and presenting a selection of results to date. A priority of the study design was obtaining in-depth information on driving behavior, permitting the exploration of diverse research questions. A tailor-made data acquisition system collected very comprehensive data. A total of 287 drivers/riders participated. The sample size restricts the addressable research topics to common behaviors in everyday driving and limits the generalizability of results. However, the data are extensive and promising analyses have already been performed. The results show differences between European countries for distracting activities, seatbelt use, and looking behavior towards cyclists at urban intersections. Moreover, it shows that European drivers engage less in mobile phone use than U.S. drivers. It is likely that European drivers differ in other ways, also—highlighting the dataset's value for developing and implementing targeted safety measures, for the E.U. and its individual countries. Based on the comparison of the different studies, the paper introduces the general conceptual framework for naturalistic driving studies, providing insight in the relation between the scope of a naturalistic driving study and the key methodological choices on sample selection and data acquisition system.